Policy Formulation for the Empowerment of Indigenous Communities in Tana Toraja Regency, South Sulawesi Province - Pajala, Samuel; Handoko, V Rudy; Sadono, Teguh Priyo (Kirana Publisher (KNPub), 2025)
This study analyzes the formulation of empowerment policies for Indigenous Peoples in Tana Toraja by examining how policies are designed, whose interests are represented, and what ideal model is expected by indigenous communities. Using a descriptive qualitative approach, data were collected through in-depth interviews with key customary actors representing different positions in the Toraja social structure. The results show that current policy formulation remains dominated by a top-down bureaucratic logic, resulting in participation that is administrative rather than substantive. Indigenous communities articulated four major interests—recognition, meaningful involvement, cultural protection, and regulatory clarity—reflecting the need for alignment between state law and customary law. The findings also reveal that economic empowerment cannot be separated from Toraja cultural continuity, as cultural norms shape social relations and resource management. Based on these findings, this study proposes the Pajala Indigenous Model (PIM), a co-productive policy framework that integrates state and customary authority across all stages of the policy cycle. The model emphasizes cultural alignment, equality in dialogue, and the central role of customary leadership as the basis of policy legitimacy. This study contributes a contextualized framework for indigenous policy formulation and offers practical direction for strengthening empowerment programs in Tana Toraja.